Understanding the role of influencers’ credibility in social media and its impact on consumers’ purchase intentions - Nascimento, Joana Duarte Neto Pires do (2019)
Digital media and the internet, in particular, have developed into a massive vehicle for consumer-generated communications. In these contexts, consumers are no longer only passive subjects in the marketing exchange process. Else than consuming content, they increasingly create, share and distribute information to other consumers through digital platforms. The fast growth of social media over the last decades has boosted the adoption of influencer marketing. This type of marketing brought companies new opportunities to expose themselves and strengthen relationships with customers. However, there is some lack of knowledge regarding the drivers that influence the effects of the influencer. In this sense, the current dissertation intents to understand how the characteristics of digital influencers, concerning various dimensions of credibility, affect the consumers' purchase intentions, comparing low and high product involvement. The present study was developed in an exploratory and quantitative way, in which a survey was conducted with 1924 valid responses obtained. The final results indicate that, for low-involvement products, all the credibility related characteristics, namely expertise, trustworthiness, attractiveness and popularity, influence consumers' purchasing intentions. Moreover, it was confirmed that an increase in the influencer’s credibility might increase the user’s purchase intentions. Contrarily, for high-involvement products, only trustworthiness and attractiveness affect purchase intentions, and increases in the credibility of the influencer might not have such a significant impact on purchase intentions.